(untitled) (Archeomatica, 2012)
"Un tuffo nel passato, attraverso un’esperienza multisensoriale, per conoscere e scoprire neldettaglio, le realtà storiche di Ercolano e Pompei prima dell’eruzione vesuviana del 79 d.C.Questa la mission del MAV, struttura che nasce nel cuore di Ercolano e che garantisce una nuovamodalità di fruizione culturale. Il visitatore sarà trasportato in un contesto virtuale ricostruitofedelmente, grazie all’uso delle più moderne tecnologie...” A blast from the past, through a multisensory experience, to learnand discover in detail the historical realities of Herculaneum andPompeii before the eruption of Vesuvius in 79 AD. This is the missionof the MAV structure that was created in the heart of Herculaneumand ensures that a new mode of cultural enjoyment. Visitors will betransported in a virtual context faithfully reconstructed through theuse of the latest technologies .